Hydrogen Sulfide and Carbon Monoxide Tolerance in Bacteria - Sofia S. Mendes; Vanessa Miranda; Lígia M. Saraiva (MDPI AG, 2021)
Hydrogen sulfide and carbon monoxide share the ability to be beneficial or harmful molecules depending on the concentrations to which organisms are exposed. Interestingly, humans and some bacteria produce small amounts of these compounds. Since several publications have summarized the recent knowledge of its effects in humans, here we have chosen to focus on the role of H2S and CO on microbial physiology. We briefly review the current knowledge on how bacteria produce and use H2S and CO. We address their potential antimicrobial properties when used at higher concentrations, and describe how microbial systems detect and survive toxic levels of H2S and CO. Finally, we highlight their antimicrobial properties against human pathogens when endogenously produced by the host and when released by external chemical donors.